2018
DOI: 10.1016/j.eswa.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Combining K-Means and a genetic algorithm through a novel arrangement of genetic operators for high quality clustering

Abstract: Knowledge discovery from data demands that it shall be the data themselves that reveal the groups (i.e. the data elements in each group) and the number of groups. For the ubiquitous task of clustering, K-MEANS is the most used algorithm applied in a broad range of areas to identify groups where intra-group distances are much smaller than inter-group distances. As a representative-based clustering approach, K-MEANS offers an extremely efficient gradient descent approach to the total squared error of representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 26 publications
0
51
0
4
Order By: Relevance
“…In particular, to analyze and compare the effectiveness and the performance of the initial population of SeedClust, two other initial population methods are used for the experiments: the initial population method of GenClust, and the density-based and K-means++ (distance-based) initialization population method (named as SeedClust (Distance), its chromosome representation and operations are the same as SeedClust, and K-means++ [14,15,55] is used for the initial seeds). In our experiment, so far, we used the improved K-means++ (density-based) for the seed selection of the initial population, and we could see that SeedClust clearly outperformed the other two existing techniques that were used in this study, as shown in Figure 2.…”
Section: Experiments Resultsmentioning
confidence: 99%
“…In particular, to analyze and compare the effectiveness and the performance of the initial population of SeedClust, two other initial population methods are used for the experiments: the initial population method of GenClust, and the density-based and K-means++ (distance-based) initialization population method (named as SeedClust (Distance), its chromosome representation and operations are the same as SeedClust, and K-means++ [14,15,55] is used for the initial seeds). In our experiment, so far, we used the improved K-means++ (density-based) for the seed selection of the initial population, and we could see that SeedClust clearly outperformed the other two existing techniques that were used in this study, as shown in Figure 2.…”
Section: Experiments Resultsmentioning
confidence: 99%
“…where P m > 0 is the mutation probability, P(L j (t)) > 0 is the selection probability defined by Equation (18), and ∑ N j=1 P(L j (t)) = 1.…”
Section: Convergencementioning
confidence: 99%
“…A disadvantage of K-Means is that it is easy to fall into local optima. As a remedy, a popular trend is to integrate the genetic algorithm [7,8] with K-means to obtain genetic K-means algorithms [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. K-Means is also combined with fuzzy mechanism to obtain fuzzy C-Means [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…In [38], an algorithm of artificial bee colony was executed to mimic an intelligent foraging conduct of honey bee swarms. In [40], a k-means was optimized through a GA, which esteems the impact of isolated points. Several studies also suggested a number of approaches for NN optimization by GA [41][42][43][44].…”
Section: Literature Review On Multi-modal Emotion Recognitionmentioning
confidence: 99%